Spatial and temporal variability in Mediterranean climate over the last millennium from vermetid isotope records and CMIP5/PMIP3 models - Amitai, Yael; Yam, Ruth; Montagna, Paolo; Devoti, Saverio; López Correa, Matthias; Shemesh, Aldo (Global and Planetary Change, 2020)
Stable isotope compositions of oxygen (δ18O) and carbon (δ13C) of the aragonite skeleton of the reef-building gastropod Dendropoma petreaum provide high-resolution records of the Mediterranean climate over the last millennium. In particular, the isotopic composition of vermetid cores collected from the west and east Mediterranean reveals that the different regions have had distinct thermal and primary production behaviors throughout the last millennium. The rate of warming in the recent Industrial Period is variable among the different regions of the Mediterranean Sea. The δ18O-derived Sea Surface Temperature (SST) anomalies show that the Eastern Mediterranean surface temperature is increasing much more rapidly than in the Western Mediterranean. Additionally, the signals of the Little Ice Age and of the Medieval Climate Anomaly are more apparent in the western and in the central Mediterranean while they are almost absent in the eastern Mediterranean. We aim to reconcile the SST temporal and spatial pattern with the variability of the North Atlantic Oscillation (NAO) and the South Asian Monsoon (SAM) climate systems by analyzing coupled atmosphere-ocean models from the CMIP5/PMIP3 projects that simulate the global climate of the past 1000 years. We show that even though the NAO is more dominant in the western Mediterranean SST, its latitudinal movement, on a centennial time scale, is evident in the eastern Mediterranean SST signal. We also discuss the Atlantic water inflow role in the observed similarities of the surface productivity signals and the Suess effect that prevail the Industrial Period signal in all regions of the Mediterranean.
CRIS-Team Scopus Importer:2020-03-27
Keywords: CMIP5/PMIP3 models; Dendropoma petreaum; Last Millennium; Mediterranean Sea; Vermetid